Ambient temperature structure of phosphoketolase from Bifidobacterium longum determined by serial femtosecond X‐ray crystallography. Issue 4 (28th March 2023) - Nakata, Kunio; Kashiwagi, Tatsuki; Kunishima, Naoki; Naitow, Hisashi; Matsuura, Yoshinori; Miyano, Hiroshi; Mizukoshi, Toshimi; Tono, Kensuke; Yabashi, Makina; Nango, Eriko; Iwata, So
Abstract : Ambient temperature structures of B. longum phosphoketolase holoenzyme and its complex with a putative inhibitor, phosphoenolpyruvate, demonstrated striking conformational change of the loop at the entrance to the active‐site pocket compared with known cryogenic temperature phosphoketolase structures. This structural change highlighted the reaction mechanism and substrate specificity of this enzyme. Abstract : Phosphoketolase and transketolase are thiamine diphosphate‐dependent enzymes and play a central role in the primary metabolism of bifidobacteria: the bifid shunt. The enzymes both catalyze phosphorolytic cleavage of xylulose 5‐phosphate or fructose 6‐phosphate in the first reaction step, but possess different substrate specificity in the second reaction step, where phosphoketolase and transketolase utilize inorganic phosphate (Pi ) and d ‐ribose 5‐phosphate, respectively, as the acceptor substrate. Structures of Bifidobacterium longum phosphoketolase holoenzyme and its complex with a putative inhibitor, phosphoenolpyruvate, were determined at 2.5 Å resolution by serial femtosecond crystallography using an X‐ray free‐electron laser. In the complex structure, phosphoenolpyruvate was present at the entrance to the active‐site pocket and plugged the channel to thiamine diphosphate. The phosphate‐group position of phosphoenolpyruvate coincided well with those of xylulose 5‐phosphate and fructose 6‐phosphate in the structures of their complexes with transketolase. The most striking structural change was observed in a loop consisting of Gln546‐Asp547‐His548‐Asn549 (the QN‐loop) at the entrance to the active‐site pocket. Contrary to the conformation of the QN‐loop that partially covers the entrance to the active‐site pocket (`closed form') in the known crystal structures, including the phosphoketolase holoenzyme and its complexes with reaction intermediates, the QN‐loop in the current ambient structures showed a more compact conformation with a widened entrance to the active‐site pocket (`open form'). In the phosphoketolase reaction, the `open form' QN‐loop may play a role in providing the binding site for xylulose 5‐phosphate or fructose 6‐phosphate in the first step, and the `closed form' QN‐loop may help confer specificity for Pi in the second step.